The "Good Life" project implemented at the Marie Curie-Skłodowska University in Lublin as an example of universal design - Katarzyna Ewa Skalska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
This article presents the experience of the Marie Curie-Skłodowska University in the field of universal design at the higher education level. Universal design in education assumes creating programs, materials, but also an environment accessible to students with different needs arising from the style of learning, age, health status, language skills, life and cultural experiences. The idea of universal design has been used in the preventive project "Good Life". The primary goal of the project was preventing suicidal behavior among academic youth. The activities undertaken in accordance with the idea of universal design were addressed to the entire academic community and were based on a four-link operation model: student, peer group, academic teachers, disabled persons' support team.